Computed tomography is superior to radiography for detection of feline elbow osteoarthritis. (November 2021) - Ley, Charles J.; Leijon, Alexandra; Uhlhorn, Margareta; Marcelino, Leticia; Hansson, Kerstin; Ley, Cecilia
Abstract: Elbow osteoarthritis (OA) is common in cats and radiography is typically used for diagnosis. However computed tomography (CT), with its multiplanar three-dimensional characteristics, could have significant advantages for assessment of OA compared to radiography, particularly early in the disease process. The study objectives were to compare radiography and CT to histologic OA changes, investigate the stage of OA that radiography and CT detect, and search for specific changes in CT images strongly predictive for feline elbow OA. Right elbows from 29 cats were evaluated by radiography and CT, and articular cartilage lesions graded histologically and macroscopically. Three further joints were sampled to specifically evaluate the morphology of the anconeal process. Macroscopic, radiographic and CT OA diagnosis were compared to the reference standard histologic OA that was divided into mild, moderate and severe. Osteophytic spurs on the lateral margin of the anconeal process could be reliably measured in CT images (intra-class correlation 0.79) and when ≥0.5 mm had high sensitivity for moderate/severe histologic OA, moderate sensitivity for mild histologic OA and high specificity for all stages of OA. In moderate/severe histologic OA both radiography and CT subjective OA diagnosis had moderate to very high sensitivity. However, in mild histologic OA CT grading had low sensitivity and radiography did not detect OA. In conclusion, CT of the feline elbow including measurement of osteophytes on the anconeal process lateral margin is superior to radiography for OA detection and should be considered for OA diagnosis, particularly when mild OA changes are of interest. Highlights: Computed tomography grades correlated to histologic articular cartilage grades. Anconeal osteophytes were reliably measured using computed tomography. Lateral anconeal osteophytes ≥0.5 mm predicted osteoarthritis. Radiography had poor sensitivity for detecting mild osteoarthritis.